Residue of Organophosphate Insecticide in Strawberry - Abdurachman, Ardestya Verta; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
Strawberry (Fragaria, sp) is very popular and delightful fruit in Indonesia. Nowadays Ciwidey County of South Bandung Region has been well known as one of the biggest producer of strawberry in West Java province and as one of tourist destination offers a concept of agrotourism activity where visitors are allowed themselves to pick any ripe strawberry fruit up directly from the plant in the farm. The usage of organophosphate insecticide to increased a quantity of product during harvest and as a pest control materials, it becomes a residue which can jeopardize the consumer’s health. The research is done to observe and to know the contents of the residue of organophosphate insecticide in strawberry farm of the agro-tourism. Samples are obtained directly from 1000 sqm – 5000 sqm strawberry farm for three days in a row. The analysis method used a tool of Chromatography Gas and its extraction used homogenizer with acetone and hexane as a solvent base on Method of Standard Analysis of Pesticide Residue, Commissioner of Pesticide 1997. Insecticide Organophosphate from the group chlorpirifos and profenofos are common use in Ciwidey. Therefore only these two types are targeted for further investigation. The result of research shows on both washed and un-washed strawberry fruit the existence of residue chlorpirifos at 0,027 ppm average in washed fruit and 0,0048 ppm in un-washed fruit while the profenofor residue is 0,0547 ppm in un-washed fruit and 0,029 ppm in washed fruit. The values are still below Maximum Residue Limit (MRL) by Codex Alimentarius. The fruit washing process by submerging can reduce insecticide residue at 40%-60%.